Passively Q-switched erbium-doped fiber laser utilizing tungsten oxide as a saturable absorber - Nady, Ahmed; Salhi, Mohamed; Harun, Sulaiman Wadi (Optical Society of America, 2019)
We demonstrated a passively Q-switched fiber laser utilizing tungsten oxide (WO3) thin film as a saturable absorber (SA). The WO3-SA was sandwiched as a polymer composite film between fiber ferrules in an erbium-doped fiber cavity. WO3 exhibits high nonlinear optical response characterized by an appropriate modulation depth of 10% and a saturation intensity of 100 MW/cm2. The fiber cavity starts to generate a stable pulse train whereby as the pump power increases from 45 to 165 mw, the repetition rate increases from 16.75 to 56.3 kHz, while the pulse width decreases from 13.8 to 4.3 µs. The Q-switched laser generated maximum pulse energy of 6.6 nJ obtained at 165 mW, which was the maximum pump power available by the used laser diode. This is, to the best of our knowledge, the first demonstration of a Q-switched fiber laser based on the WO3-SA, which could contribute as a new potential SA material in the field of pulsed fiber lasers. © 2019 Optical Society of America.